Existence and symmetries of solutions in Besov-Morrey spaces for a semilinear heat-wave type equation - Almeida, Marcelo F. de; Precioso, Juliana C. P. [UNESP] (Elsevier B.V., 2015)
This paper considers a semilinear integro-differential equation of Volterra type which interpolates semilinear heat and wave equations. Global existence of solutions is showed in spaces of Besov type based in Morrey spaces, namely Besov-Morrey spaces. Our initial data is larger than the previous works and our results provide a maximal existence class for semilinear interpolated heat-wave equation. Some symmetries, self-similarity and asymptotic behavior of solutions are also investigated in the framework of Besov Morrey spaces. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Fractional partial differential equation; Riemann-Liouville derivative; Symmetries; Self-similarity; Besov-Morrey spaces